Disease and Degeneration of Aging Neural Systems that Integrate Sleep Drive and Circadian Oscillations - Singletary, Kris; Naidoo, Nirinjini (Frontiers in Neurology, 2011)
Sleep and circadian activity rhythms become irregular with age which are characterized by fragmented sleep during the night and increased daytime sleepiness. These changes lead to a reduction in the quality of life due to cognitive impairments and emotional stress. More importantly, severely disrupted sleep and circadian rhythms have been associated with an increase in disease susceptibility. Many of the same brain areas affected by neurodegenerative diseases include the sleep and wake promoting systems. Any advances in our knowledge of these sleep/wake networks are necessary to target neural areas or connections for therapy. This review will discuss research that uses molecular, behavioral, genetic and anatomical methods to further our understanding of the interaction of these systems.